Pengaruh Bukti Fisik dan Jaminan Terhadapi Kepuasan Nasabahi BSB Capem Sako Kenten - Lestari, Fitriani Indah; Kasih, Yulizar (MDP Student Conference, 2025)
This study aims to examine the influence of the Tangible and Assurance variables on Customer Satisfaction at Bank Sumsel Babel Capem Sako Kenten. The method used is quantitative, utilizing questionnaires and direct observation, involving 60 respondents who have used the services for more than 6 months. The results indicate that all variables have a positiive and significant influence both partially and simultaneously on customer satisfaction.